Solar thermal and electricity. A state of the art (2020)
The objective of this contribution is to provide a state-of-the-art on research in solar thermal electricity systems. This objective is achieved using Scopus, and the softwears “Publish or Perish” and “VOSviewer”. The results of the research show the behavior of scientific productivity in this area. As well as the most productive thematic areas. Nations that lead the research in the generation of electric power on a large scale, using solar thermal energy. Network of scientific collaboration among nations, referring to the research of electricity generation through solar thermal energy. Correlation network among the most productive authors, in this subject within the Scopus directory. Most cited articles by each of the main journals that disseminate this theme. Conceptual bases of the generation of electricity with solar thermal energy. Properties of thermal energy storage technologies (TES) in power plants with parabolic solar concentrators or solar concentration towers. Current technologies and trends. Technological trends. Trends in the global energy market.